Social responsibility and governance in screen golf: How do they shape image, trust, and loyalty? - Kim, Se-Won (Edelweiss Applied Science and Technology, 2026)
This study investigates how social responsibility and governance influence corporate image, trust, and loyalty in the screen golf service industry. Although experiential value often dominates customer evaluations in leisure services, it remains unclear whether organizational ethical and governance practices produce meaningful relational outcomes. Using survey data collected from 235 users of screen golf facilities, Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test the proposed structural relationships. The results indicate that governance significantly enhances corporate image and directly strengthens customer loyalty. In contrast, social responsibility positively affects trust but does not exert a direct impact on corporate image or loyalty. Corporate image significantly increases trust, and trust serves as a critical predictor of loyalty. These findings suggest that consumers differentiate between governance-based operational credibility and socially responsible intentions when forming evaluations. The study concludes that governance transparency plays a central role in shaping favorable consumer responses, while social responsibility contributes indirectly through trust formation. Practical implications highlight the importance of communicating governance systems clearly and embedding responsible practices into service delivery. Theoretical implications for ESG research in leisure service contexts are also discussed.